Wilson elnök szerepe az Osztrák-Magyar Monarchia szétzúzásáról szóló geopolitikai döntés megszületésében - Gulyás László (Geopolitikai szemle, 2019)
The Austrian-Hungarian Monarchy, as a member of the “five powers concert” established at the 1815 conference in Vienna, played an important role in the geopolitical balance of the world. The Entente made a very important geopolitical decision in July 1918, in Versailles: to disessamble the Austrian‒Hungarian Monarchy, and thus to annihilate the five powers concert. The paper presents the role of president Wilson in this decision.